Given that d/dx(cosx)=-sinx show that d/dx(secx)=secx(tanx)

  • Google+ icon
  • LinkedIn icon

let y=sec(x) = 1/(cos(X)) = cos(x)-1

Thus dy/dx = -1(cos(x))-2(-sinx) = sin(x)/(cos(x))2

= 1/cos(x)  x  sin(x)/cos(x)


Owain D. 11 Plus Maths tutor, A Level Maths tutor, GCSE Maths tutor, ...

About the author

is an online A Level Maths tutor who has applied to tutor with MyTutor studying at Bristol University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss